Identifying women veterans with unhealthy alcohol use using gender‐tailored screening. (28th February 2018) - Hoggatt, Katherine J.; Simpson, Tracy; Schweizer, Catherine A.; Drexler, Karen; Yano, Elizabeth M.
Abstract : Background and Objectives: To assess the impact of gender‐tailored alcohol screening criteria. Methods: Among N = 1, 349 women, we calculated the proportion screening positive for unhealthy alcohol use with non‐tailored versus gender‐tailored criteria (a gender‐tailored binge‐drinking item, lower screen‐positive threshold, or both). Results: Three percent more women screened positive with a modified binge‐drinking question, most reporting risky drinking. Fifteen percent more women screened positive with a lower threshold; most did not report risky drinking. Discussion and Conclusions: Gender‐tailored binge‐drinking questions may improve detection of women's unhealthy alcohol use. Scientific Significance: These results can inform future efforts to improve alcohol screening for women. (Am J Addict 2018;27:97–100)